ЗАСТОСУВАННЯ УМОВНО ДВАНАДЦЯТИФАЗНОГО КЕРОВАНОГО КОМПЕНСАЦІЙНОГО ПЕРЕТВОРЮВАЧА ДЛЯ ПОСЛІДОВНОГО ПРЯМОГО ЗАПУСКУ ВІД ЕЛЕКТРИЧНОЇ МЕРЕЖІ ЧОТИРЬОХ ПОТУЖНИХ АСИНХРОННИХ МАШИН - Чиженко, О.І.; Рибіна, О.Б. (Інститут електродинаміки НАН України, Київ, 2024)
The sequential direct start-up of four asynchronous machines (AM) with a capacity of 8 MW each from a 6 kV electrical network is considered. The start-up transient modes that arise in the network as a result of such an AM start-up are investigated, as well as the possible consequences for the network. To facilitate the direct start of AM with a capacity of 8 MW, it is proposed to use a conditional twelve-phase controlled compensating converter, which limits the amount of starting overcurrents in the network. References 10, figures 6.